Determinação da toxicidade do gossipol em folículos ovarianos de ovelhas - Câmara, Antônio Carlos Lopes (Universidade Federal Rural do Semi-Árido, 2015)
Gossypol is a polyphenol compound produced by the pigment glands of cotton plants (Gossypium spp.) and presents proven deleterious action on spermatogenesis, rodent´s estrous cycle, granulosa cells steroidogenesis in pigs, early termination of pregnancy and embryonic development. However, the effects on sheep ovaries were not yet studied. This study was divided into two stages and aimed to determine in vitro and in vivo effect of gossypol on sheep ovarian follicles. In the first stage, eight ovarian fragments from each ewe were cultured in α-MEM supplemented culture and subjected to three concentrations of gossypol-acetic acid (5, 10 and 20 µg/mL) for periods of 24 hours and seven days. In vitro action of gossypol resulted in a significant reduction in the number of viable ovarian follicles of all development stages, and a significant increase in the number of atretic follicles after 24 hours and seven days of cultivation (p < 0,01). In the latter it was remarkable the absence of viable antral follicles and the primordial follicles presented less than 50% of viability. In the second stage, we used twelve crossbred ewes, which were randomly divided into two groups and fed diets containing cottonseed cake or not (control group). Concentrate feed was offered at a rate of 1.5% of body weight of the animal for 63 days. Concentrations of total and free gossypol in cottonseed cake was 3.28 mg/g and 0.11 mg/g, respectively. Throughout the trial period no animal showed clinical signs of toxicosis. There was no interference on progesterone concentrations, weight, weight gain and ovaries measurements. Only occasional changes on vaginal cytology, hematological and biochemical parameters were noted. However, treatment with gossypol was responsible for significant reduction in the number of viable ovarian follicles (20.6% in treated sheep and 65.1% the control group) and significant increase in the number of atretic follicles (79.4% in treated sheep and 34.9% in control group), interfering at all stages of follicular development (p < 0,01). In conclusion, the gossypol promotes direct damage to the ovarian follicles of sheep, resulting in an increase on the proportion of atretic follicles and reduction of viable follicles both in vitro and in vivo
Determination of gossypol toxicity on sheep ovarian foliccles
Keywords: Sheep; Gossypium spp.; Antinutriciona factor; Follicles atretic; Cottonseed cake; Ovelhas; Gossypium spp.; Fator antinutriciona; Folículos atrésicos; Torta de algodão; CIENCIAS AGRARIAS::MEDICINA VETERINARIA